The R132H mutation in IDH1 promotes the recruitment of NK cells through CX3CL1/CX3CR1 chemotaxis and is correlated with a better prognosis in gliomas. Issue 5 (25th January 2019) - Ren, Feifei; Zhao, Qitai; Huang, Lan; Zheng, Yujia; Li, Lifeng; He, Qianyi; Zhang, Chaoqi; Li, Feng; Maimela, Nomathamsanqa R; Sun, Zhi; Jia, Qingquan; Ping, Yu; et al.
Abstract: Mutations in the isocitrate dehydrogenase (IDH) 1 gene, especially the R132H mutation, have been reported to be associated with a better prognosis in glioma patients. However, the underlying molecular mechanisms are not yet well understood. Many factors may contribute to differences in the survival of IDH1 wild‐type and IDH1 mutant glioma patients, in which immune components play a potentially important role. In this study, we analyzed The Cancer Genome Atlas (TCGA), and the Chinese Glioma Genome Atlas (CGGA) databases, as well as glioma patient‐derived tumor samples. We found that there was a higher infiltration of natural killer (NK) cells in IDH1 mutant glioma patients, and this was correlated with a better prognosis. We also showed that IDH1‐R132 tumor cells had higher expression levels of the chemokine CX3CL1. This arises as a result of the conversion of α‐ketoglutarate to R(‐)‐2‐hydroxyglutarate by the IDH1 mutant and the resultant phosphorylation of nuclear factor kappa B. Knockdown of CX3CL1 decreased the migration of NK cells. In addition, the high levels of expression of CX3CL1 were positively correlated with glioma patient survival in the TCGA and CGGA databases, and in the clinical samples. Overall, our data have identified a novel mechanism in which R132H mutation of the IDH1 gene serves as a tumor suppressor by promoting the recruitment of NK cells through CX3CL1/CX3CR1 chemotaxis. Abstract : Our study showed that the IDH1‐R132H mutation in gliomas promoted the expression of p‐NF‐κB, which upregulated chemokine CX3CL1 expression, thus promoting the recruitment of NK cells. There was also potent evidence for NK cell immunotherapy in IDH1‐R132H mutant glioma patients.